1977
DOI: 10.1128/iai.15.1.132-137.1977
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Escherichia coli and Vibrio cholerae enterotoxins by an inhibitor of protein synthesis

Abstract: Enterotoxigenic Escherichia coli or Vibrio cholerae 569B (Inaba) grown in the presence of the antibiotic lincomycin, an inhibitor of protein synthesis, produced elevated levels of heat-labile enterotoxin or choleragen, respectively, as assayed by both vascular permeability factor and capacity to elicit fluid accumulation in rabbit ileal loops. This induction of enterotoxin did not reflect either a coupling of lincomycin resistance with increased enterotoxigenicity or an effect of lincomycin on cellular release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 16 publications
4
27
0
Order By: Relevance
“…It is clear, however, that toxin production in these strains is not proportional to bacterial mass, either in the presence or absence of lincomycin. Variation in the amount of increase of enterotoxin production induced by lincomycin was also reported for the LT of enterotoxinogenic E. coli [1]. The reason for this variation may become apparent after the mechanism of stimulation of enterotoxin production by lincomycin is elucidated.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…It is clear, however, that toxin production in these strains is not proportional to bacterial mass, either in the presence or absence of lincomycin. Variation in the amount of increase of enterotoxin production induced by lincomycin was also reported for the LT of enterotoxinogenic E. coli [1]. The reason for this variation may become apparent after the mechanism of stimulation of enterotoxin production by lincomycin is elucidated.…”
Section: Resultsmentioning
confidence: 75%
“…It has been reported that lincomycin, an inhibitor of protein synthesis, stimulates the production of cholera enterotoxin (CT) and Escherichia coli heat-labile enterotoxin (LT) [1][2][3]. Lincomycin causes an increase in the rate of synthesis of CT and thus the amounts of both extracellular and intracellular CT were significantly increased [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that previous workers were unsuccessful in purifying it because it is found intracellularly in relatively small amounts, and they did not exploit the affinity chromatographic properties of agarose in its isolation. It is conceivable that greater quantities can be isolated using lincomycin induction [20] and/or other cultural conditions. 241…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be emphasized that only extracellular heat-labile enterotoxin was determined in this study. Other methods for obtaining a high yield of enterotoxin have been tested, such as induction by the DNA inhibitor mitomycin C [13] and by the protein inhibitor lincomycin [ 14 ]. The combination of such methods with efficient cultivation methods may result in greatly facilitated production ofE.…”
Section: Discussionmentioning
confidence: 99%